Glutamic Acid Application for Enhancement of Growth and Productivity of Okra Plant (Abelmoschus esculentus L. Moench) - Eva Septiyana; Nintya Setiari; Sri Darmanti (Biogenesis: Jurnal Ilmiah Biologi, 2019)
Red okra fruit has high nutritional value and fiber but still has low production. Monosodium glutamate (MSG) consists of sodium and glutamic acid. In plants, sodium can role of replacing potassium, stomata physiology, and chlorophyll biosynthesis. Glutamate as the nitrogen donor in primer metabolism and gibberellic acid precursor. The assumption that MSG in plants has a positive impact. This research aimed to examine the effect of MSG and the optimum dosage for enhances of growth and production. This research was conducted with Completely Randomized Designs (CRD) with one factor, is the MSG dosage (0, 3, 6, and 9 g). Quantitative data were analyzed using analysis of variant (ANOVA) dan Duncan’s Multiple Range Test (DMRT) at a 95% confidence level. The result shows that the MSG treatment enhances the growth of the okra based on parameters of plant’s height, fresh weight of plant, dry weight of plant and the width of the leaf and enhances the production of the okra based on the flowering time, the number of the flower, the number of the fruit, the percentage of flower becoming fruit, the weight of fruit, width of fruit, and the diameter of the fruit. The optimal dosage of MSG for okra production and growth is 3 g/plant.